D-Meson azimuthal anisotropy in midcentral Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Leardini, Lucia; Ohlson, Alice; Pachmayer, Yvonne C.; et al. (Physical review letters, 2018)
The azimuthal anisotropy coefficient v2 of prompt D0, D+, D*+, and D+s mesons was measured in midcentral (30%-50% centrality class) Pb-Pb collisions at a center-of-mass energy per nucleon pair √sNN=5.02 TeV, with the ALICE detector at the LHC. The D mesons were reconstructed via their hadronic decays at midrapidity, |y|<0.8, in the transverse momentum interval 1<pT<24 GeV/c. The measured D-meson v2 has similar values as that of charged pions. The D+s v2, measured for the first time, is found to be compatible with that of nonstrange D mesons. The measurements are compared with theoretical calculations of charm-quark transport in a hydrodynamically expanding medium and have the potential to constrain medium parameters.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
S. Acharya, V. Anguelov, M. Arslandok, H. Beck, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, M. Kim, S. Klewin, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 01.07.2019